Analysis of scientific publications related to Hepatitis B prevention in the last decade: 2013-2023 - Julien, Anoucheka; Sousa Neto, Antonio Rosa de; Carvalho, Ana Raquel Batista de; Freitas, Daniela Reis Joaquim de; Moura, Luana Kelle Batista; Moura, Maria Eliete Batista; Bezerra, Simone Maria Muniz da Silva; Magalhães, Rosilane de Lima Brito (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: The World Health Organization estimates that chronic infection with the Hepatitis B Virus globally affects approximately 296 million individuals, with 1.5 million new infections yearly. Those affected often remain asymptomatic for extended periods but may inadvertently transmit Hepatitis B Virus to others. Aim: To analyze scientific publications related to the prevention of hepatitis B from 2013 to 2023. Outlining: A bibliometric study with a quantitative approach analyzing 333 articles using the Bibliometrix R package and its web interface Biblioshiny. Results: Articles were predominantly published in 2018 and 2019, with the Journal of Viral Hepatitis being the primary scientific journal. These articles were authored by 2,467 individuals from 810 institutions, emphasizing Udice - French Research Universities. Among the 81 countries identified, China figured prominently. The articles accumulated a total of 8,964 citations. The KeyWords Plus™ highlighted a focus on infection and its transmission pathways, notably vertical/perinatal, immunization against infection, and treatment using antiretrovirals. Implications: The need for new studies focused on educational interventions related to hepatitis B prevention was identified, including the creation, application, and evaluation of educational technologies.